Тенденції розвитку автомобільних сенсорів швидкості - Бритковський, Василь (КІНПАТРІ ЛТД, 2013)
Actual automobile variants of speed and angular position with contactless sensor magnetically toothed rotor magnetic circuit with reverse shift.
Trends in automobile speed sensor